Mechanical design of humanoid robot platform KHR-3 (KAIST Humanoid Robot 3: HUBO) - Ill-Woo Park; Jung-Yup Kim; Jungho Lee; Jun-Ho Oh (5th IEEE-RAS International Conference on Humanoid Robots, 2005, 2005)
KHR-I has been developed on the purpose of research about biped walking. It has 21 DOF without hands and head, which has 12 DOF in legs, 1 DOF in torso, and 8 DOF in arms. The objective of KHR-2 (41 DOF) was to develop the humanoid which can walk on the living-floor with human-like appearance and movement. KHR-3 has the purpose that it has more human-like features, movements and human-friendly character. Mechanical design of KHR-3 is presented on this paper. The design concept, lower body design, upper body design and actuator selection of joints are included in this paper. We have developed and published KHR-I and 2 in last three years. KHR3 platform is based on KHR-2. It has 41 degree of freedom (DOF), 125 cm height, and 55 kg weight. The differences from KHR-2 are mechanical stiffness and detailed design of the frame in the mechanical point of view. Stiffness of the frame is increased and detailed design about joints and link frame has been modified or redesigned. We introduced exterior art design concept on KHR-2 in beginning, and the concept has been implemented on KHR-3 in mechanical design stage